Los hábitos alimenticios y su incidencia en el aprendizaje de las niñas y niños de preparatoria, primer grado de educación general básica del centro educativo “Cesar Borja Lavalle” de la provincia de Lago Agrio, cantón Cuyabeno. Periodo lectivo 2013-2014”. Lineamientos alternativos - Camacho Chora, Viviana Margoth (2015)
This thesis refers to "FOOD HABITS AND ITS IMPACT ON BASIC GENERAL EDUCATION FIRST DEGREE CHILDREN LEARNING "CESAR BORJA LAVALLE" LAGO AGRIO PROVINCE CUYABENOCANTON. PERIOD 2013-2014". ALTERNATIVE GUIDELINES, It was made according to the provisions of the Regulation of Academic Board of the Loja National University. The General objective: to Sensitize Parents on the impactBasic General Education First Degree Children Learning. The methods used for the preparation of this research work were : Scientist, Inductive- Deductive , Analytic - Synthetic, Descriptive and Statistical Model , which served them help efficiently achieve the goal. The techniques and instruments used were an Inquiry that parents of children from School , First Grade Students General Education School " Cesar BorjaLavalle " in the province of LagoAgrio was applied to establish the Habits food in children ; and an Observation applied to children of School , First Grade Students General Education School " Cesar BorjaLavalle " to assess their learning , for which a pre- structured guide was developed based on Hubs Components of learning and learning Hubs . We conclude that: 100 % of respondents Parent Family, say their responsibilities to create good eating habits in your children is to select and buy good food, 92 % regulate mealtimes, make nice 78% of the time meals; and 46% establish rules of behavior at the table. Regarding the observation guide, the results determine that: 63% of girls and children have seen an equivalent Learning Highly Satisfactory, 35% and 2% Satisfactory Unsatisfactory